Dye-Sensitized TiO2 as Heterogenous Visible Light Photocatalyst for the Hydroxylation of Aryl Boronic Acids - Argüello, Juan Elias (2023)
Herein, we report the preparation of a variety of dye-sensitized TiO2 and its application as a heterogeneous photocatalyst for the oxidative hydroxylation of boronic acids and esters to synthesize phenols. Several organic dyes, namely eosin Y, rose bengal, purpurin, alizarin blue, fluorescein and riboflavin were combined with TiO2. The nanohybrid TiO2-eosin Y showed the best results. Furthermore, we demonstrated a synergistic association between dyes and TiO2 that improves its photocatalytic properties. This methodology resulted compatible for aryl boronic acids with both electron-withdrawing and electron donor groups on the aromatic ring. Thus, the reactions were performed under heterogeneous photocatalytic conditions, employing visible light, saturated oxygen atmosphere, short reaction time, acetonitrile and water as environmentally friendly solvents, to produce the corresponding phenols in very good to excellent isolated yields. Finally, we proposed a mechanism where the selective excitation of EY associated with TiO2 using visible light and the formation of the superoxide anion play a main role in this reaction.